Changes of Brain Functional Connectivity in End-Stage Renal Disease Patients Receiving Peritoneal Dialysis Without Cognitive Decline - Chang, Ting-Yu; Wu, Hsin-Hsu; Li, Yi-Jung; Liu, Ho-Ling; Yeh, Chih-Hua; Jian, Hui-Shan; Huang, Kuo-Lun; Lee, Tsong-Hai; Tian, Ya-Chung; Wu, Changwei W. (Frontiers in Medicine, 2021)
Background Functional connectivity detected by resting-state functional magnetic resonance image (R-fMRI) helps to discover the subtle changes of brain activities. End-stage renal disease (ESRD) patients on hemodialysis (HD) have impaired brain networks. However, the functional changes of brain networks in ESRD patients undergoing peritoneal dialysis (PD) have not been fully delineated, especially among those with preserved cognitive function. Therefore, it is worth knowing the brain functional connectivity in PD patients by using R-fMRI. Methods This case-control study prospectively enrolled 19 ESRD patients receiving PD and 24 age- and sex- matched controls. All participants without a history of cognitive decline received mini-mental status examination (MMSE) and brain 3-T R-fMRI. Comprehensive R-fMRI analyses included graph analysis for connectivity and seed-based correlation networks. Independent t-tests were used for comparing the graph parameters and connectivity networks between PD patients and controls. Results All subjects were cognitively intact (MMSE > 24). Whole-brain connectivity by graph analysis revealed significant differences between the two groups with decreased global efficiency (Eglob, p < 0.05), increased betweenness centrality (BC) (p < 0.01), and increased characteristic path length (L, p < 0.01) in PD patients. The functional connections of default-mode network (DMN), sensorimotor network (SMN), salience network (SN), and hippocampal network (HN) were impaired in PD patients. Meanwhile, in DMN and SN, elevated connectivity was observed in certain brain regions of PD patients. Conclusion ESRD patients receiving PD had specific disruptions of functional connectivity. In graph analysis, Eglob, BC, and L showed significant connectivity changes compared to the controls. DMN and SN might have the most prominent alterations among the observed networks, with both decreased and increased connectivity regions. Our study confirmed that significant changes in cerebral connections existed in cognitively intact PD patients.